EVALUATION OF HEART RATE AUTONOMOUS REGULATION IN PATIENT AFTER MYOCARDIAL INFARCTION - S. A. Bolduyeva; V. S. Zhuk; I. A. Leonova; T. Y. Burak; M. V. Samohvalova; A. V. Shabrov (Российский кардиологический журнал)
200 coronary patients after a myocardial infarction were studied in order to examine the influence myocardial infarction (MI) localization and depth, as well as sex and age, complications, concomitant conditions and treatment may have on heart rate variability (HRV). HRV was evaluated on the 10-14th day of myocardial infarction with a 5-minutes ECG record. Women demonstrated longer RR intervals, predominant CV, dRR, NN50 and RMSSD, tended to have higher TP and SD, LF/HF, IN and IRV were greater than in men. Thus women had higher parasympathetic tone. Age showed no influence on HRV, most likely because almost all patients were within the same age group (52-62 years). In inferior-posterior MIs as compared to anterior %LF was decreased and %HF, %VLF were higher, reflecting greater vagal tone in inferior MIs. In Q-MIs decreased SD and TP were observed. Concomitant hypertension increased the impact of %VLF, implying switch of regulation to a lower humoral-metabolic level . Concomitant diabetes mellitus decreased NN50, LF/HF, VPR, IRV and IN, reflecting cardiac neuropathy. Exacerbation of heart failure demonstrated worsened HRV and markedly decreased %HF and HFnu, implying parasympathetic influences being most depressed. Early postinfarctional angina was associated with greater LFnu and %LF, also reliably decreasing %VLF which is mot likely due to significant stress of the sympathetic branch. b-Blockers increased RR, increasing RMSSD, NN50 and %HF, demonstrating vagal influence under their action. ACE inhibitors shortened RR increasing HFnu and decreasing %VLF implying activation of the parasympathetic branch of the nervous system with simultaneously decreased humoral and metabolic influences. There were no differences in HRV depending on previous MIs and treatment with aspirin or nitrates.